Effects of Land-Use Dynamics on Soil Organic Carbon and Total Nitrogen Stock, Western Ethiopia - Yitayh Leul; Mohammed Assen; Shimeles Damene; Asmamaw Legass (Applied and Environmental Soil Science)
Soil organic carbon (SOC) and total nitrogen (TN) stock are key indicators of soil quality in tropical regions; however, their status is often degraded, especially due to massive deforestation in natural forest areas associated with extensive agricultural land use. The aim of this study was to investigate the dynamics of SOC and TN stock in different land-use systems in the Abobo woreda, Western Ethiopia. To analyze their status, 80 disturbed (composite) and 45 undisturbed soil samples were collected from the top 20 cm of soil in five major land-use types: natural forestlands, grasslands, recently developed commercial farmlands, old commercial farmlands, and small-scale cultivated lands. The results showed that SOC stock varied significantly across the different land-use types, with mean stock ranging from 32.23 Mg·ha−1 in recently developed commercial farmlands to 54.54 Mg·ha−1 in natural forestlands. The mean TN stock ranged from 2.54 Mg·ha−1 in recently developed commercial farmlands to 4.63 Mg·ha−1 in natural forestlands. With natural forestlands as a baseline and the duration ranging in age from 15 to 45 years since land-use conversion, the mean annual absolute rates of change in SOC and TN stock loss were 0.49, 1.49, 0.39, and 0.45 Mg·ha−1·yr−1 and 0.05, 0.14, 0.03, and 0.04 Mg·ha−1·yr−1 for grasslands, recently developed commercial farmlands, old commercial farmlands, and small-scale cultivated lands, respectively. The results of this study revealed that soil disturbance during forestland conversion to tillage enhanced the decomposition rate of organic matter in recently developed commercial farmlands. Nevertheless, after agricultural abandonment and vegetation restoration, the SOC and TN stock capacities were enriched in the old commercial farmlands. It is, therefore, important to effectively restore vegetation and implement sustainable land-use management practices.